Vai trò của giáo dục trong quá trình chuyển tiếp từ trường học sang việc làm của thanh niên Việt Nam - Trần Thị Thu, Vân (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
The successful transition from school to employment marks a significant milestone in one’s life, as participation in the workplace provides financial independence, social networks, and self-esteem. However, few empirical estimates have been conducted in Vietnam. This paper examines the relationship between educational attainment and the school-to-work transition of school-leavers from 15 to 29 years old in Vietnam using data is from School to Work Transition Surveys 2015. This paper employs the diagram of the Kaplan-Meier estimator and the survival function with the exponential proportional hazard model to examine the impacts of education on the transition to the first paid employment. Then, this paper investigates the driving factors of the probability choosing occupation using a multinomial logit model is used for sub-data including those with the first paid job. The author found that person with high education results in faster entering the first paid employment and higher probability of entering the wage employment with a contract, female find job faster than male laborers, and family background, particularly parental education, does not affect the school to work transition process.
Keywords: Transition; From school to work; Employment; Youth; Education; Vietnam